1999
DOI: 10.1246/bcsj.72.839
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Extremely Stable Tris(6-methoxy-1-azulenyl)methyl Cation and a Series of Di(1-azulenyl)phenylmethyl and (1-Azulenyl)diphenylmethyl Cations Stabilized by Methoxy Substituents

Abstract: Extremely stable carbocations, tris(6-methoxy-1-azulenyl)methyl (8), bis(6-methoxy-1-azulenyl)(4-methoxyphenyl)methyl (9a), and (6-methoxy-1-azulenyl)bis(4-methoxyphenyl)methyl (10a) cations and a series of di(1-azulenyl)phenylmethyl and (1-azulenyl)diphenylmethyl cations having methoxy substituents on each phenyl group, i.e., di(1-azulenyl)(4-methoxyphenyl)methyl (9b) and (1-azulenyl)bis(4-methoxyphenyl)methyl (10b) cations and 3-methyl-1-azulenyl (9cand 10c) and 3,6-di-t-butyl-1-azulenyl (9d and 10d) analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The easily accessible organic tetracation incorporating the 21-thiatriazuliporphyrinf rame provides ar are instanceo fm acrocyclic tetracations precedented by an electron-deficient tetracationic cyclophane [23] (cyclobis-(paraquat-p-phenylene)w idely used in the construction of molecular machines or switches. [24] By considering the apparent importance of acyclic azulene-stabilized cations, dications, and trications, [25][26][27][28][29][30] as well as the azulene cation in the design of electronic materials, these readily available macrocyclic polycation species may be regardeda sacontrollable building block for conductive or semiconductive applicationso rf ormation of stabilized electrochromic and polyelectrochromic materials. [31,32] Experimental Section General Dichloromethane was distilled from calcium hydride before use as the reaction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The easily accessible organic tetracation incorporating the 21-thiatriazuliporphyrinf rame provides ar are instanceo fm acrocyclic tetracations precedented by an electron-deficient tetracationic cyclophane [23] (cyclobis-(paraquat-p-phenylene)w idely used in the construction of molecular machines or switches. [24] By considering the apparent importance of acyclic azulene-stabilized cations, dications, and trications, [25][26][27][28][29][30] as well as the azulene cation in the design of electronic materials, these readily available macrocyclic polycation species may be regardeda sacontrollable building block for conductive or semiconductive applicationso rf ormation of stabilized electrochromic and polyelectrochromic materials. [31,32] Experimental Section General Dichloromethane was distilled from calcium hydride before use as the reaction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The signals in the UV/Vis spectrum of 6 a‐2 (Figure 4, inset), which bears the characteristic features of free azulene, are replaced by a set of intense bands in the visible region with the most intense signal located at 588 nm. The spectrum of 5 a resembles those of azulene‐containing methylium salts 3133…”
Section: Methodsmentioning
confidence: 95%
“…It has been suggested that this increase can be attributed to the steric effect and less to hyperconjugation [16]. The contribution of the donor substituents such as OMe [22,23] or NMe 2 [24,25] to phenyl and/or azulene is more important. As shown in Scheme 7, for cation 10 (R ph = R az = Me 2 N) the charge is distributed between the resonance structures A, A' and A", namely methylium, tropylium, and ammonium ions.…”
Section: Bmentioning
confidence: 99%